Economies Based on Reward Sharing: A Case Study in Indonesia's Tertiary Sector - Umi Karomah Yaumidin (Journal of Indonesian Social Sciences and Humanities, 2008)
Reward-sharing activities are well known in the business world, particularly for businesses relying on trust. Today, the basic concepts of Islamic economics are widely used not only in the banking sector but also in other economic sectors. In Indonesia, the concept of profit and loss sharing (PLS), contract sharing and revenue sharing can be seen as an another model to accelerate growth after cyclic downturns. There are at least three reasons why it is important to examine this concept. First, how it affects lower investment inflows, whether domestic or foreign investment. High corruption, high risk and uncertainty are the most common reasons and influencing factors for investors wanting to invest in Indonesia, although Indonesian governments have been working hard to reduce these handicaps. Second, there are difficulties for small enterprises in getting funds from formal financial institutions and this contributes to company bankruptcies. As is commonly known, financial institutions require interest fees for credit but many small businesses cannot meet this requirement because they have not enough assets to quarantine their credit.